Assessing educational disparities in COVID-19 related excess mortality in Spain: a population register-linked mortality study - Pulido, José; Donat, Marta; Moreno, Almudena; Politi, Julieta; Cea-Soriano, Lucía; Sordo, Luis; Mateo-Urdiales, Alberto; Ronda, Elena; Belza, María José; Barrio, Gregorio; Regidor, Enrique (Frontiers in Public Health, 2024)
Introduction: Data on mortality increase during COVID-19 pandemic by socioeconomic position of people are limited. This study examines this increase in Spain during the epidemic waves of 2020 and 2021.Methods: Overall mortality and cause-specific mortality during the 2017-2019 prepandemic period and during four epidemic periods of 2020 and 2021 (first, second, third-fourth, and fifth-sixth waves) by educational level (low, medium and high) and broad age groups (25-64, 65-74 and 75+) were calculated. The mortality increase during each epidemic period in each educational level, compared to the pre-pandemic period, were estimated using mortality rate ratios (MRR) from Poisson regression.Results: An inverse educational gradient in overall mortality in any period was found, but not for COVID-19 mortality in some age groups. In those 75+, high-educated people showed the higher COVID-19 mortality during the first wave. In the 25-64 age group, low and high-educated people showed the highest and lowest overall mortality increment, respectively. The MRR were 1.21 and 1.06 during the first wave, and 1.12 and 0.97 during the last epidemic period. In the 65-74 age group, high-educated people during the first wave and medium-educated people during the rest of the epidemic periods showed the highest overall mortality increment. In the 75+ age group, high and loweducated people showed the highest and the lowest overall mortality increment, respectively, except during last epidemic period.The different educational patterns of COVID-19 mortality by age contributed to the heterogeneity of findings on excess overall mortality by education during the COVID-19 pandemic.